Diagnóstico dos agroecossistemas na microbacia hidrográfica do rio Pirapora - município de Piedade/SP - Schneider, Fernando (Universidade Federal de São Carlos, 2012)
The present work was aimed at making the diagnosis of 25 Agroecosystems located in the Pirapora river micro basin, in the Piedade municipality, State of São Paulo, focusing particularly on the adopted management practices. The socioeconomic, productive and environmental implications of these practices were analyzed and contextualized in the scenario of São Paulo State agriculture. The focus in the watershed, besides their legal aspects, reflects its importance as a geographical until priority actions for integrated management, conservation and natural resource management. In this study we sought to define the indicators that reflect the complexity of management were studied based on the method proposed by MESMIS, as well as by systematic methodological experience Agronomic Institute of Paraná IAPAR, systemic approach. The main results arising from systematized this work were: a significant presence of family farmers in the region, the incompatibility of management techniques adopted in Agroecosystems in relation to environmental and soil characteristics of the region, the weakness in the organization among the farmers, the narrow market for the sale restricted to the middleman, the heavy dependence on external inputs to the system resulting from a conventional farming, the use of pesticides banned, the impairment of water resources and public health of residents for limited use in the preservation of water sources and lack of sanitation. These factors indicate that the diagnosed type of agriculture currently practiced in the region is undermining the sustainability of Agroecosystems due to the degradation of natural resources and, consequently, of their own agricultural activities in the watershed.
Diagnosis of agroecosystems in the micro basin of pirapora river - piedade São Paulo
Keywords: Agroecologia; Microbacia hidrográfica; Agroecossistemas; Piedade (SP); Manejo; Agricultura familiar; Diagnóstico; Watershed; Agroecosystem; Diagnosis, Management, Family farming, Agriculture, Piedade; CIENCIAS AGRARIAS